Modeling of residential indoor PM2.5 exposure in 37 counties in China. (July 2018) - Du, Yanjun; Wang, Yanwen; Du, Zonghao; Zhang, Yi; Xu, Dandan; Li, Tiantian
Abstract: It is critical to estimate the exposure to indoor air pollution of residents spending most of their time in such microenvironments. However, the understanding regarding PM2.5 exposure in residential indoor environments is very limited. In this study, we collected participants' basic information and time–activity patterns, as well as details of other factors related to indoor air pollution exposure, through questionnaires presented to a large population in 37 counties of China. Continuous monitoring of ambient PM2.5 concentrations was performed using an environmental fixed-site monitoring network. Residential indoor PM2.5 concentrations were predicted using a mass balance model based on the data obtained. Evaluation of continuous daily average residential indoor PM2.5 exposure doses for large populations during winter revealed concentrations ranged from 67 to 195 μg/m 3 . Finally, differences in residential indoor PM2.5 exposure between northern and southern China were investigated. The results suggested that residential indoor PM2.5 concentrations in northern China, associated with heating, were higher than in the south. The established model could be important for improved understanding of human exposure to indoor PM2.5 air pollution. Graphical abstract: Image 1 Highlights: PM2.5 exposure in indoor environments was evaluated in 37 Chinese counties. A mass balance model was applied to predict residential indoor PM2.5 concentrations. Residential indoor PM2.5 exposure in north China was elevated due to the heating. The established model was important for understanding the human indoor exposure. Abstract : Residential indoor PM2.5 exposure was evaluated in 37 Chinese counties, which is important for improved understanding of human indoor exposure.